Electronics, Communications and Networks V Proceedings of the 5th International Conference on Electronics, Communications and Networks (CECNet 2015) - Hussain, Amir.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book comprises peer-reviewed contributions presented at the 5th International Conference on Electronics, Communications and Networks (CECNet 2015), held in Shanghai, China, 12-15 December, 2015. It includes new multi-disciplinary topics spanning a unique depth and breadth of cutting-edge research areas in Electronic Engineering, Communications and Networks, and Computer Technology. More generally, it is of interest to academics, students and professionals involved in Consumer Electronics Technology, Communication Engineering and Technology, Wireless Communication Systems and Technology, and Computer Engineering and Technology.
Design Gysel Power Divider/Combiner with Harmonic Suppression Using Cross-Shaped Transmission Line -- Detecting Communities Based on Edge-Fitness and Node-Similarity in Social Networks -- An Adaptive Spatial-Temporal Error Concealment Scheme based on H.264/AVC -- Research on Data Recording and Playback System for Virtual Testing Framework -- Research on a Credit Reservation Mechanism for Concurrent Multi-service -- A MAC Protocol for Medical Emergency Monitoring Wireless Body Area Networks -- Weighted Modularity on k-path Graph.
Keywords: Electric power production; Computer networks .; Telecommunication; Electrical Power Engineering; Computer Communication Networks; Communications Engineering, Networks